Design and evaluation of an advanced virtual reality system for visualization of dentistry structures - Dias, Diego Roberto Colombo; Neto, Mário Popolin [UNESP]; Brega, José Remo Ferreira [UNESP]; Gnecco, Bruno Barberi; Trevelin, Luis Carlos; De Paiva Guimarães, Marcelo (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents the development of an application created to assist the teaching of dental structures, generate rich content information and different manners of interaction. An ontology was created to provide semantics informations for virtual models. We also used two devices gesture-based interaction: Kinect and Wii Remote. It was developed a system which use intuitive interaction, and it is able to generate three dimensional images, making the experience of teaching / learning motivating. The projection environment used by the system was called Mini CAVE. © 2012 IEEE.
Keywords: Content information; Gesture-based interaction; Intuitive interaction; Semantics Information; Three dimensional images; Virtual models; Virtual reality system; Wii remote; Information science; Semantics; Three dimensional; Virtual reality; Design